IMAJI KEMATIAN YANG TERGAMBAR DALAM PUISI-PUISI KARYA PHILLIS WHEATLEY - Rumbajan, Axel Gilby; Sigarlaki, Stephanie J.; Lasut, Theresia M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  This study which is entitled â€œThe Images of Death depicted in Phillis Wheatley Poemsâ€ focusing on the types of imagery that are appeared in every selected poem written by Phillis Wheatley. The writer chooses five poems by Phillis Wheatley that related with death as the themes of the poems and analyzes them by using intrinsic approach to discover types of imagery of every poem. This study uses the theory of Wellek and Warren (1976) about the relationship of literature and life.Â  The purpose of this study is to identify and analyze the types of imagery that are appeared in every selected poem written by Phillis Wheatley. The result of this study can be summarized as follows: there are five types of imagery which are found in five selected poems written by Phillis Wheatley, that are : visual imagery, tactile imagery, auditory imagery, kinesthetic imagery and organic imagery. Types of imagery depicted in Phillis Wheatleyâ€™s selected poems are dominated by visual imagery, auditory imagery and kinesthetic imagery.Â Keyword : Poems, Intrinsic Approach, Imagery, Death, Phillis Wheatley